Earth System Science in the Anthropocene - Ehlers, Eckart; Krafft, Thomas (Springer Berlin Heidelberg, 2006)
This work provides an in-depth perspective and update on special topics in Global Environmental Change in relation to Human Security. It offers an overview of new Joint Projects of the four International Global Change Programmmes and on research efforts in Germany. It is also an up-to-date report on emerging necessities in Global Environmental Change research, and a collection of suggestions for its future evolution.
Includes bibliographical references and index
Keywords: Aufsatzsammlung; Ökosystem; Anthropogener Einfluss; Umweltveränderung